Elevated serum uric acid affects myocardial reperfusion and infarct size in patients with ST-segment elevation myocardial infarction undergoing primary percutaneous coronary intervention. Issue 5 (May 2018) - Mandurino-Mirizzi, Alessandro; Crimi, Gabriele; Raineri, Claudia; Pica, Silvia; Ruffinazzi, Marta; Gianni, Umberto; Repetto, Alessandra; Ferlini, Marco; Marinoni, Barbara; Leonardi, Sergio; De Servi, Stefano; Oltrona Visconti, Luigi; et al.
Abstract : Aims: Elevated serum uric acid (eSUA) was associated with unfavorable outcome in patients with ST-segment elevation myocardial infarction (STEMI). However, the effect of eSUA on myocardial reperfusion injury and infarct size has been poorly investigated. Our aim was to correlate eSUA with infarct size, infarct size shrinkage, myocardial reperfusion grade and long-term mortality in STEMI patients undergoing primary percutaneous coronary intervention. Methods: We performed a post-hoc patients-level analysis of two randomized controlled trials, testing strategies for myocardial ischemia/reperfusion injury protection. Each patient underwent acute (3–5 days) and follow-up (4–6 months) cardiac magnetic resonance. Infarct size and infarct size shrinkage were outcomes of interest. We assessed T2-weighted edema, myocardial blush grade (MBG), corrected Thrombolysis in myocardial infarction Frame Count, ST-segment resolution and long-term all-cause mortality. Results: A total of 101 (86.1% anterior) STEMI patients were included; eSUA was found in 16 (15.8%) patients. Infarct size was larger in eSUA compared with non-eSUA patients (42.3 ± 22 vs. 29.1 ± 15 ml, P = 0.008). After adjusting for covariates, infarct size was 10.3 ml (95% confidence interval 1.2–19.3 ml, P = 0.001) larger in eSUA. Among patients with anterior myocardial infarction the difference in delayed enhancement between groups was maintained (respectively, 42.3 ± 22.4 vs. 29.9 ± 15.4 ml, P = 0.015). Infarct size shrinkage was similar between the groups. Compared with non-eSUA, eSUA patients had larger T2-weighted edema (53.8 vs. 41.2 ml, P = 0.031) and less favorable MBG (MBG < 2: 44.4 vs. 13.6%, P = 0.045). Corrected Thrombolysis in myocardial infarction Frame Count and ST-segment resolution did not significantly differ between the groups. At a median follow-up of 7.3 years, all-cause mortality was higher in the eSUA group (18.8 vs. 2.4%, P = 0.028). Conclusion: eSUA may affect myocardial reperfusion in patients with STEMI undergoing percutaneous coronary intervention and is associated with larger infarct size and higher long-term mortality. Abstract : Supplemental Digital Content is available in the text